Analisis Determinan Neraca Perdagangan Di 5 Negara Asean - Sri Afriyanti; Dewi Zaini Putri (Universitas Negeri Padang, 2021)
This study aims to analyze the influence of energy consumption, economic growth, exchange rates and inflation on the trade balance in 5 ASEAN countries. The data used is panel data from 2009 – 2019, and is collected through data documentation and literature studies obtained from related institutions and agencies. This study use panel regression, with use variables: energy consumption, economic growth, exchange rate, inflation and trade balance. This study found that (1) energy consumption has a significant and negative effect on the trade balance, (2) economic growth has no significant and negative effect on the trade balance, (3) the exchange rate has a significant and positive effect on the trade balance, (4) ) inflation has no significant and negative effect on the trade balance and (5) simultaneously all independent variables in this study have a significant effect on the trade balance.